DEVELOPMENT AND MANAGEMENT OF SMART POWER GRID EFFICIENCY WITH 5G GENERATION TECHNOLOGY (Journal of Pharmaceutical Negative Results, 2023)
Due to the management and deployment of the 5G technology in the smart power grid, there will be some impacts affecting the cost and energy efficiency, especially in the areas of not reliable power grid and not available, in addition, the operators are not experts to use the 5G technology infrastructure. The 5G infrastructure is affected by several factors such as Large Cells, Unmanned Arial Vehicle (UAV), Capital Expenditures CAPEX, and Operating Expenditures OPEX costs. Results obtained show that an off-grid network with 5G can be constructed with good efficiency and low effects on the wide range wireless network connectivity, especially for users living in rural and small areas of low income instead of wire connectivity in addition the application of renewable solar energy sources will let the off-grid operating efficiently in emergencies conditions. With this technology, the cost and time of the power grid network distribution will be optimized and minimized. Meanwhile, the smart power grid management which will be offered by the 5G has more reliability and produce smart adaptive patterns with solar energy.